Pengaruh Kompetensi dan Kepuasan Guru Terhadap Kinerja Guru SMA Negeri di Wilayah Bakorwil I Jawa Timur - Arifin, Moh (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2017)
This research talks about the Influence of Competence and Master’s Satisfaction Performance of High School Teachers in Bakorwil I Region of East Java. The population of research is 1012 high school teachers. By using the Slovin formula with a tolerance of 5%, the sample size was 287 respondents. Test model with Least Square Estimate estimation (GLS), structural equation model (SEM) analysis, proportional random sampling method and Amos 22 software, on 287 respondents. The test results show the model (fit) seen from the GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF values, respectively 0.942, 0.913, 0.964, 0.981, 0.064 and 1.588 are all within the expected value range. The model is acceptable. The results showed that: 1). Teacher competence has a significant effect on teacher’s satisfaction. 2). Teacher competence has a significant effect on teacher performance. 3). Teacher satisfaction has a significant effect on teacher performance.4). Teacher competence has an indirectly significant influence on teacher performance through teacher’s satisfaction. Keywords: teacher competence, satisfaction, teacher performance